Pengaruh CR, DER, dan ROE Terhadap Harga Saham Perusahaan LQ45 di BEI - Reni Nuraeni; Benny Barnas; Fifi Afiyanti Tripuspitorini (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to examine the effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Return On Equity (ROE) on the stock prices of LQ45 companies on the IDX in 2016-2020. The research method used is a quantitative method with an associative approach. The population in this study is 68 companies. The number of samples as many as 24 companies that meet the research criteria using purposive sampling method. The analytical method used is panel data regression. The results showed that partially the CR and DER variables had no significant effect on stock prices. ROE variable partially positive and significant effect on stock prices. Meanwhile, simultaneously, the variables CR, DER, and ROE have a significant effect on stock prices.